Evaluation Of Reinforced Concrete’s Beam’s Capacity With Open Crack And Variation of Cover Thickness Using UPV And Hammer Test - Saifoe El Unas; Sugeng P. Budio; M. Taufik Hidayat; Achfas Zacoeb; Ristinah Ristinah; Roland Martin S.; Christin Remayanti N.; Ahmad Rizqol Mahbub (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2013)
Defect in building’s structure can be analyzed by non-destructive method or NDT, such as UPV Test and hammer test. Furthermore the UPV, hammer test, compressive strength test, flexural test and statistical analysis show the accuration of quality test result with the NDT method. The specimen used is brick-formed with the dimension of 15x20x140 cm and the variation of cover thickness. Average relative error of hammer test of cylinder test is about 2,83% - 7,32%. While UPV’s average relative error of cylinder sample is 4,74% - 55,05%. Based on statistical analysis, hammer test shows there is no significant difference, while UPV test shows that there is significant difference. Calculation of compressive strength before and after flexural loading obtains a number of relative error, in hammer test 5,58% - 10,53% and UPV test 7,35% - 13,05%.